Diyarbakirli Aşik Niyazi'nin Hayati, Sanati Ve Şiirlerinden Örnekler - Akın, Bülent (Journal of Alevism-Bektashism Studies, 2010)
In this study the works of art and life of Aşık Niyazi who is the one of the minstrel of Diyarbakır region and the decreasing number of the Turkmen Alawi villages' minstrelsy tradition were examined. Furthermore the light of these datas, some information about Turkmen-Alawi villages and their history were given. By the help of this, the core of the study was trying to be impowered. The informnation about Aşık Niyazi's life and his poems was gathered from his family, intimates and villagers. 350 poems were compiled and 60 of them were analyzed in order to ascertain his art features. These datas were examined deeply.
Keywords: keyword